Denosumab Chemotherapy for Recurrent Giant-Cell Tumor of Bone: A Case Report of Neoadjuvant Use Enabling Complete Surgical Resection. (30th July 2013) - Agarwal, Amit; Larsen, Brandon T.; Buadu, Lawrence D.; Dunn, Jack; Crawford, Russell; Daniel, Jonathan; Bishop, Maria C.
Abstract : Giant-cell tumor of the bone (GCTB) is a rare neoplasm that affects young adults. The tumor is generally benign but sometimes can be locally aggressive. There are no standardized approaches to the treatment of GCTB. Recently, the RANKL inhibitor denosumab has shown activity in this tumor type. We present the case of a young female who presented with locally advanced disease and was successfully managed with the neoadjuvant use of denosumab allowing for surgical resection of the tumor that was previously deemed unresectable. Following surgery, the patient is being managed with continued use of denosumab as 'maintenance, ' and she continues to be free of disease. Our case highlights a novel approach for the management of locally advanced and aggressive giant cell tumor of the bone.